Man and body in the history of the modern age (Historia, 2021)
Apparently it is the same for everyone. Ever since scientists from the most diverse disciplines discovered the body, the number of conferences, conventions, and collo-quia dealing with it has multiplied. And everywhere the experience is the same: there is no such thing as the body. 1 Four years ago, we han felt that this gave us good reason to complain, when we reported on a first symposium accompanying a research project at the Freie Universit1it in Berlin, entitled, 'Man and Health in the History of the Modern Age'.2 Invited to a further round-table discussion at the beginning of De-cember 1981 were representatives of social history, of the history of "mentalites" and population, of medicine, art, and architecture, of folklore and ethnology, of historical behavioural research, sociology, and physical anthropology, and of occupational, social, and preventative medicine from France, Scandinavia, Switzerland, West Ger-many, and Berlin. Although each of the three days was devoted to a firmly outlined theme concerning the body, thus endeavouring to counteract the parcelling of the body and body-related themes, it appeared that the speakers as well as those partici-pating in the discussion were to a great extent infected by that development which has most drastically taken place in medicine.
Keywords: Body-related ideas; Lifestyles; History; Convention reports; Round-table discussions; Sexuality revolution; Infant Mortality; Convention on Man and Health in the History of the Modern Age; Modern history